Historical Perspectives and Evolution of Menstrual Terminology - Chodankar, Rohan R.; Munro, Malcolm G.; Critchley, Hilary O. D. (Frontiers in Reproductive Health, 2022)
Abnormal uterine bleeding (AUB) is a common, chronic, and debilitating condition affecting women worldwide with an adverse impact on their quality of life. Until the last decade, the "menstrual" terminology used to describe both normal and abnormal uterine bleeding and its underlying causes was inconsistent, creating considerable confusion, and potentially hampering clinical management as well as designing and interpreting basic, translational, epidemiological, and clinical research in women with menstrual problems. In this article, we explore the history and evolution of menstrual terminology and discuss the two International Federation of Gynecology and Obstetrics (FIGO) systems on i.e., A) menstrual terminology and definitions B) and the causes of AUB, achieved through international consensus of relevant stakeholders through a long multistage journey.